VD_FINDINFO Jug / 2016 / 113 vom 3. November 2015 - VD Tribunal cantonal (2015)
PEINE COMPLÉMENTAIRE, SÉJOUR ILLÉGAL, DÉLIT CONTINU, ADMISSION PARTIELLE | 115 al. 1 let. b LEtr, 10 CPP (CH), 398 al. 3 let. b CPP (CH)